Involvement of KLF14 and egr-1 in the TGF-beta1 action on Leydig cell proliferation - Gonzalez, Candela Rocio (2013)
Transforming growth factor β1 (TGF-β1) is a pleiotropic cytokine that modulates cell homeostasis. In Leydig cells, TGF-β1 exerts stimulatory and inhibitory effect depending on the type I receptor involved in the signaling pathway. The aim of the present work was to study the signaling mechanisms and the intermediates involved in the action of TGF-β1 on TM3 Leydig cell proliferation in the presence or absence of progesterone. The MTT assay showed that the presence of progesterone in the culture media lead to a proliferative effect that was blocked by Ru 486, an inhibitor of progesterone receptor; and ALK-5 did not participate in this effect. TGF-β1 (1. ng/ml) increased the expression of p15 (an inhibitor of cell cycle) in TM3 Leydig cells, and this effect was blocked by progesterone (1 μM). The expression of PCNA presented a higher increase in the cell cultured with TGF-β1 plus progesterone than in cells cultured only with TGF-β1.Progesterone induced the gene expression of endoglin, a cofactor of TGF-β1 receptor that leads to a stimulatory signaling pathway, despite of the absence of progesterone response element in endoglin gene. In addition, the presence of progesterone induced the gene expression of egr-1 and also KLF14, indicating that this steroid channels the signaling pathway into a non-canonical mechanism. In conclusion, these findings suggest that the proliferative action of TGF-β1 involves endoglin. This co-receptor might be induced by KLF14 which is probably activated by progesterone.